OPTIMIZATION OF ACTIVE ACIDITY FOR PEPTIDES DERIVATION IN THE PRODUCTION OF FERMENTED MILKS - Tomovska, J.; Gruevska, N.; Tomovska, N. (Journal of Engineering & Processing Management, 2010)
There are three parameters that influences hydrolyses on milk and fermented milk products. Active acidity (pH) is one of that factors that determines speed of reaction and can influence on specific enzyme substrate. In production of yogurt, hydrolyses is measured by amount of peptides on different pH value. Maximum pH is determined to obtain maximum amount of peptides in yogurt. In order to stop the change in pH value during hydrolysis, the reaction it should be lead out in buffer system. An important parameter for hydrolysis of proteins is the distribution of the weight of the molecule obtained by hydrolysis of peptidite. For milk fermentation were used three different mixture (or combination) of microbiological starter cultures: Lactobacillus delbrueckii subs. bulgaricus and Streptococcus thermophilus; Lactobacillus acidophilus, Bifidobacterium bifidus and Streptococcus thermophilus; Lactococcus lactic subsp. cremoris and Lactococcus lactis subsp. lactis, production by Chr. Hansen’s Laboratories. The task was subsequent measurement of pH value on different temperatures and time incubation of milk by different cultures. Quantity of amino group released in the process of microbiological growing in milk can be easy followed with OPA method, reaction on o-phtaldialdehid in β-merkaptoetanol. Specimens of yogurt were prepared from cow, sheep and goat milk. The measurement of optimal pH with usage three culture were: first mixture on the 430C, fermentation of some pH= 4,3 for 4 hours; second on 370C fermentation some pH= 4,5 for 5 hours and third mixture on 220C and 300C temperature fermentation of some pH= 5,45 for 12 and 8 hours. Amount of total peptides in same type of milk and same pH, same temperature with different mixture of starter culture were different.